The Influence of L2 Proficiency on Bilinguals' Creativity: The Key Role of Adaptive Emotion Regulation Strategies During the COVID-19 Pandemic - Yang, Yilong; Wu, Shinian; Duñabeitia, Jon Andoni; Jiang, Kexin; Li, Yadan (Frontiers in Psychology, 2021)
Previous studies on second language (L2) learners have shown a bilingual advantage in creativity. The COVID-19 pandemic has brought severe psychological impact worldwide. Creativity would be critical and essential during the time of crisis. The literature in creative thinking has suggested individuals’ emotional states would affect their performance in creativity. The question of how adaptive emotion regulation (ER) strategies, which helps an individual has appropriate and stable mood states, might affect bilinguals’ creativity remains unexplored. The present study investigated this issue by measuring various indicators of the psychological impact of the COVID-19 pandemic, L2 proficiency, adaptive ER strategies, and bilinguals’ cognitive creativity (CC) and emotional creativity (EC) during the pandemic. Based on a sample of 235 participants, the results showed that bilinguals’ negative mood had significantly increased during the pandemic compared with the mood state before the pandemic. Negative mood during the pandemic was then positively associated with participants’ adaptive ER strategies. We found L2 proficiency had a direct effect on bilinguals’ cognitive flexibility, EC, and CC. L2 proficiency also influenced language learners’ CC through cognitive flexibility indirectly. These results suggested cognitive flexibility had a simple mediation effect in bilinguals’ CC. However, we further found bilinguals had different cognitive patterns in EC. L2 proficiency influenced bilinguals’ EC through cognitive flexibility indirectly only when adaptive ER strategies had a moderation effect on the association between cognitive flexibility and EC, revealing a moderated mediation mechanism in EC. However, this moderation effect was not significant in CC. Our study implies that bilinguals’ adaptive ER strategies during the COVID-19 pandemic have affected bilinguals’ EC but not CC.